2019
DOI: 10.1111/jgs.16274
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Baseline Fatigue on a Physical Activity Intervention to Prevent Mobility Disability

Abstract: OBJECTIVES Our aim was to examine the impacts of baseline fatigue on the effectiveness of a physical activity (PA) intervention to prevent major mobility disability (MMD) and persistent major mobility disability (PMMD) in participants from the Lifestyle Interventions and Independence for Elders (LIFE) study. DESIGN Prospective cohort of individuals aged 65 years or older undergoing structured PA intervention or health education (HE) for a mean of 2.6 years. SETTING LIFE was a multicenter eight‐site randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Physical activity may reduce the development of frailty by maintaining or improving physical functioning, preventing falls and developing components of the frailty syndrome. Intervention trials generally showed improvements in balance (31), mobility (32,33), or gait ability (34). However, results were mixed for fall risk, balance, functional ability, and muscle strength (32).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity may reduce the development of frailty by maintaining or improving physical functioning, preventing falls and developing components of the frailty syndrome. Intervention trials generally showed improvements in balance (31), mobility (32,33), or gait ability (34). However, results were mixed for fall risk, balance, functional ability, and muscle strength (32).…”
Section: Discussionmentioning
confidence: 99%
“…WHO recommendations suggest to promote the increase of aerobic PA time among adults and older adults in terms of MVPA min/week because it is effective in preserving mobility, even with high levels of baseline fatigue 56 . Furthermore, previous studies have suggested that eHealth interventions are mostly effective in promoting MVPA.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement factors in the pathogenesis of T2DM are insulin resistance, a deteriorated insulin secretory capacity, and a genetic background associated with excess energy intake and physical inactivity. Physical exercise, which directly protects muscle glucose metabolism and attenuates insulin resistance [38][39][40], may restore the impaired insulin secretory capacity [41] and rebuild glycemic control [42]. As mentioned above, irisin is induced by physical exercise, and given the biological activities of irisin, it is reasonable to presume that irisin is involved in the protective effects of physical training on muscular glucose metabolism.…”
Section: Muscle Glucose Homeostasis In Patients With Metabolic Diseases: a Role For Irisinmentioning
confidence: 99%